Work environment and related burnout levels: survey among healthcare workers in two hospitals of Southern Italy: Work environment and related burnout levels among healthcare workers - Lupo, Roberto; Lezzi, Alessia; Conte, Luana; Santoro, Pietro; Carvello, Maicol; Artioli, Giovanna; Calabrò, Antonino; Caldararo, Cosimo; Botti, Stefano; Carriero, Maria Chiara (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Safety in hospitals is a structural variable on which depends not only on health, but also on physical safety of patients and employees, whom are increasingly exposed to risks as a result of which they may suffer from occupational diseases and/or develop important psycho-physical consequences. The study aimed to evaluate the association between work environment and perceived burnout levels in two hospitals of Southern Italy. Method.: From March to August 2019 an observational study was carried out through a survey consisting of four sections: sociodemographic data; the Post Occupancy Evaluation (POE) questionnaire; the perception of the environment and possible causes of stress; the burnout levels perceived through the Maslach Burnout Inventory (MBI). A convenience sample of 169 healthcare workers participated in the study. All nurses (including nursing coordinators), clinicians, support staff of the "Vito Fazzi" Hospital of Lecce (Le) and "San Giuseppe da Copertino" Hospital of Copertino (Le) with at least one year of work experience and who signed the informed consent were recruited. Results. The healthcare workers involved in the survey declared limits in handling and usability of the equipment, both for the patient n=77 (45.6%) and for the healthcare worker n=75 (44.4%), a lack of visual privacy n=89 (52.6%) and acoustic n=128 (75.7%). The analysis also shows higher scores on the ’depersonalization’ scale among the health care workers of San Giuseppe da Copertino” Hospital (LE) (M= 9.36; DS= 9.439) and higher levels on the ’emotional exhaustion’ scale in the surgical areas (M= 22.0; DS= 11.86) and in the female gender (M= 23.10; DS=. 12.01). Conclusions. The study reveals a poor condition of environmental comfort and safety, which generate high levels of stress and burnout in healthcare workers. Such a study can encourage further multicenter studies.